The Use of QRIS in Improving Digital Payment Efficiency and Financial Inclusion in Indonesia - Ananda, Geby Citra (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Digital transformation in the financial sector has driven the development of non-cash payment instruments in Indonesia. The Quick Response Code Indonesian Standard (QRIS) is a QR Code-based payment system innovation standardized by Bank Indonesia to facilitate transactions, reduce costs, and improve the efficiency of digital payments. This study aims to analyze how the use of QRIS can enhance the efficiency of digital payments and expand financial inclusion in Indonesia. The research used a descriptive qualitative approach, drawing on secondary data from Bank Indonesia publications, industry reports, and academic studies. The results show that QRIS improves transaction efficiency by reducing costs, enabling interoperability, and speeding payment processes. In addition, QRIS accelerates financial inclusion, especially for MSMEs that previously had no access to formal financial services, by enabling easier onboarding to digital payment systems. This study confirms that QRIS is a strategic instrument in supporting economic digitalization and increasing financial access in Indonesia.